Monoclonal Antibody Monitoring: Clinically Relevant Aspects, A Systematic Critical Review. Issue 1 (February 2020) - Regazzi, Mario; Golay, Joseè; Molinaro, Mariadelfina
Abstract : Abstract: Monoclonal antibody (mAb) therapy does not usually lead to a clinical response in all patients and resistance may increase over time after repeated mAb administration. This lack or loss of response to the treatment may originate from different and little-known epigenetic, biomolecular, or pathophysiological mechanisms, although an inadequate serum concentration is perhaps the most likely cause, even if not widely recognized and investigated yet. Patient factors that influence the pharmacokinetics (PK) of a mAb should be taken into account. Multiple analyses of patient-derived PK data have identified various factors influencing the clearance of mAbs. These factors include the presence of antidrug antibodies, low serum albumin, high serum levels of C-reactive protein, high body weight, and gender differences among others. The same clearance processes involved in systemic clearance after intravenous administration are also involved in local first-pass catabolism after subcutaneous administration of mAbs. Therapeutic drug monitoring has been proposed as a way to understand and respond to the variability in clinical response and remission. For both classes of mAbs with anti-inflammatory and antitumor effects, dose-guided optimization based on the measurement of serum concentrations in individual patients could be the next step for a personalized and targeted mAb therapy.